2019
DOI: 10.1021/acs.jchemed.8b00381
|View full text |Cite
|
Sign up to set email alerts
|

Creating and Experimenting with a Low-Cost, Rugged System to Visually Demonstrate the Vapor Pressure of Liquids as a Function of Temperature

Abstract: A creative apparatus for use in a hands-on laboratory experiment that allows the visualization of the vapor pressure as a function of temperature is described in this paper. Inspired by homemade barometers and using simple materials that are easily accessible for teaching laboratories, a low-cost system for the establishment of the vapor-pressure curve was constructed and applied in deionized water and in car-radiator-additive samples (based on ethane-1,2-diol) at different concentrations. The system construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Studies have shown that computer simulation and visual teaching methods can present knowledge more directly, concretely, and conveniently than traditional teaching methods. Other studies have shown that computer-based teaching is conducive to students’ inquiry-based learning , and independent learning, which may improve students’ academic level. , Moreover, in the emergency context of the COVID-19 pandemic, computer-based chemistry education has been rapidly applied to online teaching. For example, Blackboard Collaborate virtual classroom package was used for online lab demonstration; Microsoft Excel was used in data-handling, processing, and analysis; augmented reality application was used in the demonstration of atomic stacking and lattice; WebVR software such as Uptale was used to create the virtual crime scene for the educational situation; embedded video questions were used for online assignments…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that computer simulation and visual teaching methods can present knowledge more directly, concretely, and conveniently than traditional teaching methods. Other studies have shown that computer-based teaching is conducive to students’ inquiry-based learning , and independent learning, which may improve students’ academic level. , Moreover, in the emergency context of the COVID-19 pandemic, computer-based chemistry education has been rapidly applied to online teaching. For example, Blackboard Collaborate virtual classroom package was used for online lab demonstration; Microsoft Excel was used in data-handling, processing, and analysis; augmented reality application was used in the demonstration of atomic stacking and lattice; WebVR software such as Uptale was used to create the virtual crime scene for the educational situation; embedded video questions were used for online assignments…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research showed that the use of experimental tools can help teachers prepare and present sufficient experiment (Orwat et al, 2016). The experimental tools can also be made using tools that are easily found and simple materials (Cybulskis et al, 2016;Papai et al, 2019). Therefore, the researcher intends to conduct a study of developing experimental tools and implementing the practicum of reaction rate determination based on gas formation to develop students' science process skills.…”
Section: Introductionmentioning
confidence: 99%